An exploration of job satisfaction amongst Maltese teachers - Gravino, Nicola (2015)
This study adds to the existing literature on the job satisfaction of Maltese teachers by using a mixed-methods approach to identify the major contributors to the job satisfaction of local teachers. Using regression analysis to analyse 374 survey responses, this study identifies the intrinsic rewards of working with young people and student achievement as the most important contributors to teachers‟ overall level of job satisfaction. Other important contributors include workload, the image of teachers portrayed in the media, collegiality, feedback and recognition, the opportunity to take on leadership roles and involvement in decision-making. Out of these important contributors, Maltese teachers are highly satisfied with working with young people, student achievement and collegiality, but are somewhat ambivalent with feedback and recognition, the opportunity to take on leadership roles and involvement in decision-making. Moreover, Maltese teachers appear to be highly dissatisfied with their workload and with the image of teachers portrayed in the media. These results were generally confirmed by information obtained from semi-structured interviews carried out with six participants. However, interview participants also identified professional development as a major contributor to teachers overall level of job satisfaction. On the basis of these findings, this study presents a number of recommendations aimed at the school management team to improve teachers‟ job satisfaction by addressing issues related to a number of school-based factors.